ANALISIS KELEMBAGAAN PASAR TEMBAKAU DI MADURA - Slamet Subari (Trunojoyo University of Madura, 2010)
In general, the purpose of this research is to find and prove the factors that cause market failure. Specifically this study aims to: (1) prove the existence of the phenomenon of cartelization; (2) prove the existence of asymmetric information; (3) prove the existence of government failure in the system of Madura tabacco trade;The results of the discussion can be summarized as follows:1. There has been an agreement among the Cigarette Factory to set a specific price level (the cartelization phenomenon). This is based on the facts that: (1) a form of order on schedule for opening of the warehouse so that it can avoid Cigarette Factory of competition with each other; (2) the facts about the distribution of the highest price level of about Rp. 33 000 to Rp. 34 000 showed there was an agreement between Cigarette Factory to set a specific price level.2. Asymmetric information occurs at different levels Madura tobacco transcations ranging from level 2 transcations between the Tobacco Factory and owners, 3-level transcations between owners with bandol and 4-level transcations between bandol with farmers. Those who dominate more information, they can be played with the market so as to capture more benefits.3. Based on data and analysis can be concluded that the government had failed to form intervention to overcome the symptoms that lead to forms of market failure in both the substance of legislation and enforcement process.